Modelagem de jogos massivos on-line como um processo de salto - Izabella Araujo Rodrigues Alves Santos (2013)
This paper addresses a methodology to model the mobility of the characters in Massively Multiplayer On-line (MMO) Games. Despite the importance of the virtual games industry, most studies in this area are superficial and merely descriptives. We propose to model the mobility of characters in the map of an MMO game as a jump process using two approaches to model the times spent in the states of the process: Parametric and Non-Parametric. Furthermore, a simulator for the mobility is presented. We analyze geographic position data of the characters in the map of the game World of Warcraft (WoW) and compare the observed and simulated data.